Creación de un Micro emprendimiento dedicado a la elaboración de productos y servicios de decoración para eventos sociales, para mejorar las condiciones de vida de madres y sus hijos con capacidades diferentes del sur de Quito. - Méndez Cajamarca, Tania Anaís (2010)
Creating the micro company dedicated to developing products and services decoration for social events will be located in the area of Quitumbe, the same which aims to improve the lives of mothers and children with disabilities in southern Quito.